Growth and investigation of quaternary III-III-III-V InGaAlAs alloy layers on InP by molecular beam epitaxy - Feng, Z.C. (2014)
Journal of the Chinese Institute of Electrical Engineering, Transactions of the Chinese Institute of Engineers, Series E/Chung KuoTien Chi Kung Chieng Hsueh K'an